Thariqah al-Qur'an in politics and dakwah: A reflection from Bapak Mohammad Natsir (1908-1993) - Mohd Noor A.Y.; Amir A.N.; Ab Rahman Z.; Mohd Kashim M.I.A.; Mohd Mokhtar A. (Innovare Academics Sciences Pvt. Ltd, 2024)
Bapak Mohammad Natsir (1908-1993) is considered as one of the prominent Muslim politicians and scholars in contemporary Muslims world. This article aims to discuss the Thariqah al-Qur'an based on historical struggle of Bapak Mohammad Natsir in the fields of politics and dakwah in Indonesia. It attempts to analyze his contributions in raising the spectra of Islamic politics and dakwah driven by his struggle in Masyumi (Muslims Consultative Council of Indonesia), and DDII (Islamic Missionary Chamber of Indonesia), as well as from his substantive writings on the political ideal and aspiration of dakwah in Islam. This research also analyzes the views of Muslim scholars on his critical contributions to the Muslim nation and his wide influence and legacy in modern history of Indonesia. The study is based on descriptive and analytical method. The study found that Pak Natsir's struggle in the Masyumi Islamic party and the Indonesian Islamic Da'wah Council (DDII) has forged an important history in political thought in Indonesia. Natsir is a legendary activist and figure who grew up in his composite history. His significant contributions to upholding the ideals of an ideal political ideology and his inclusive understanding have developed a fundamental cultural foundation for his people. His attempts to break down the fortress of the taklid, restoring the understanding of Islam and tauhid, outlining the principles of da'wah and maqasid, and developing the tradition of science have carved its name in the history of politics, da'wah and contemporary Islamic jurisprudence. 2020 Innovare Academics Sciences Pvt. Ltd. All rights reserved.